THE MUSNAD GENRE IN HADITH LITERATURE: ORIGINS, TYPOLOGY, AND METHODOLOGICAL SIGNIFICANCE (The Journal of Interdisciplinary Human Studies, 2026)
This article investigates the musnad as a distinct genre within the classicalhadith sciences, tracing its lexical origins, its technical definitions as employed inthe scholarly tradition, and the historical conditions that gave rise to its emergenceas a systematic mode of hadith compilation. The study examines the methodologicalprinciples governing musnad works, the criteria by which they are classified into selected(muntaqa), critically annotated (muʿallal), and general (ʿamm) categories, and thevarious organizational schemes applied by their compilers. Attention is also given tothe genre’s contribution to the preservation of transmission chains and its indispensablerole in the disciplines of narrator criticism (jarh wa-taʿdil) and hadith authentication.
Keywords: hadith sciences, musnad, isnad; sanad; narrator criticism; jarh wa-taʿdil; Companion narrations